(untitled) (Bangladesh Journal of Agricultural Research, 2009)
The study was conducted at Barisal and Jhalokati districts during 2007 to estimate the profitability and resource use efficiency of rnungbean production. The study was confined to randomly selected 100 mungbean farmers. It revealed that mungbean production is profitable to the farmers. The productivity of munghean at farm level was 928 kg/ha, which vas higher than national average of 680 kg/ha. Mungbean farmers received Tk. 24236 as gross margin per hectare. The net benefit received per kilogram of mungbean was Tk. 26.45. Benefit cost ratios were estimated at 2.53 and 3.56 on variable and cash cost basis. Functional analysis showed that human labour, urea and insecticides had positive significant contribution to mungbean cultivation. Mungbean farmers encountered various problems like untimely rainfall, lack of quality seed and disease and insect infestation, and needs immediate attention to reduce these problems. Key Words: Profitability, mungbean, resource use efficiency. doi: 10.3329/bjar.v33i4.2292 Bangladesh J. Agril. Res. 33(4) : 587-595, December 2008